R-spondin 3 deletion induces Erk phosphorylation to enhance Wnt signaling and promote bone formation in the appendicular skeleton - Nagano, Kenichi; Yamana, Kei; Saito, Hiroaki; Kiviranta, Riku; Pedroni, Ana Clara; Raval, Dhairya; Niehrs, Christof; Gori, Francesca; Baron, Roland (eLife, 2022)
Activation of Wnt signaling leads to high bone density. The R-spondin family of four secreted glycoproteins (Rspo1-4) amplifies Wnt signaling. In humans, RSPO3 variants are strongly associated with bone density. Here, we investigated the role of Rspo3 in skeletal homeostasis in mice. Using a comprehensive set of mouse genetic and mechanistic studies, we show that in the appendicular skeleton, Rspo3 haplo-insufficiency and Rspo3 targeted deletion in Runx2+ osteoprogenitors lead to an increase in trabecular bone mass, with increased number of osteoblasts and bone formation. In contrast and highlighting the complexity of Wnt signaling in the regulation of skeletal homeostasis, we show that Rspo3 deletion in osteoprogenitors results in the opposite phenotype in the axial skeleton, i.e., low vertebral trabecular bone mass. Mechanistically, Rspo3 deficiency impairs the inhibitory effect of Dkk1 on Wnt signaling activation and bone mass. We demonstrate that Rspo3 deficiency leads to activation of Erk signaling which in turn, stabilizes β-catenin and Wnt signaling activation. Our data demonstrate that Rspo3 haplo-insufficiency/deficiency boosts canonical Wnt signaling by activating Erk signaling, to favor osteoblastogenesis, bone formation, and bone mass.
Keywords: R-spondin; skeletal homeostasis; Erk signaling; Wnt signaling